Field research on measurement and use of trypanotolerance criteria to enhance trypanotolerant livestock productivity. 2. Recent results quantifying trypanotolerance indicators - Trail, J.C.M.; Wissocq, N.M.; D'Ieteren, G.D.M. (International Laboratory for Research on Animal Diseases, 1994)
A six year data at Mushie Ranch, Zaire was collected and analysed to quantify the relative importance of four trypanotolerance indicators (ability to control the length of time detected parasitaemic, the ability to control the intensity of parasitaemia, the ability to resist the development of severe anaemia and the ability to acquire resistance to infection). The data provides a clear picture of the pattern of trypanosome infection over the life of an N'Dama in this region of Central Africa. It has allowed the quantification of the ability of these N'Dama cattle to acquire over time a degree of resistance to trypanosome infection. It also permits the simultaneous quantification in post-weaners of the effects of capacity to control the duration and intensity of parasitaemia and capacity to resist development of severe anaemia on both an animal's requirement for trypanocidal drug treatment and its post-weaning growth. When analysis of the effects of these indicators on life-time production has been carried out, it allows appropriate weighting of post-weaner calves grazing with their dams are markedly protected from, or more resistant to, infections of both T. vivax and T. congolense.